Literature Review: Hubungan Pengetahuan terhadap Sikap Masyarakat tentang Upaya Pencegahan Penularan Tuberculosis - Fitriani Ningsih; Riska Ovany; Yuni Anjelina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Tuberculosis is still a global public health problem that is a global challenge. One of the causes of the lack of public knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers cadres about Tuberculosis, resulting in a lack of public knowledge about Tuberculosis. This study aims to explain